2013
DOI: 10.1108/imr-02-2012-0024
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative approach to understanding brand image in an international context

Abstract: Purpose – The paper aims to demonstrate the utility of qualitative research for: understanding differences in brand image across markets; the critical assessment of marketing theory; informing revisions to quantitative scales and metrics used in international branding research. This is accomplished via research on a particular case (socialist era brands in Croatia and Serbia). Design/methodology/approach – A total of 12 focus groups, cutting across two countries (Croatia and Serbia) and three age groups (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Values are crucial to establishing organizational culture (Enz, 1988;Weiner, 1988). Several authors have indicated the influence of shared values on some elements of user brand perception (Eisingerich & Rubera, 2010;Sichtmann & Diamantopoulos, 2013;Brecic et al, 2013). Frankel, Schechtman, and Koenigs (2006) operated a regulated set of values to compare images of optimal leadership between two divisions of the education industry: independent elementary schools and colleges/research universities in the USA and Canada.…”
Section: The Role Of Ethics Policy and Shared Values In The Perceived Image Of The Universitymentioning
confidence: 99%
See 1 more Smart Citation
“…Values are crucial to establishing organizational culture (Enz, 1988;Weiner, 1988). Several authors have indicated the influence of shared values on some elements of user brand perception (Eisingerich & Rubera, 2010;Sichtmann & Diamantopoulos, 2013;Brecic et al, 2013). Frankel, Schechtman, and Koenigs (2006) operated a regulated set of values to compare images of optimal leadership between two divisions of the education industry: independent elementary schools and colleges/research universities in the USA and Canada.…”
Section: The Role Of Ethics Policy and Shared Values In The Perceived Image Of The Universitymentioning
confidence: 99%
“…Several authors have pointed out the importance of the shared values of employees in aspects of consumer behaviour (Maxham & Netemeyer, 2003) and, in particular, that of shared values of the consumer and various elements of brand perception (Eisingerich & Rubera, 2010;Sichtmann & Diamantopoulos, 2013;Brecic et al, 2013).…”
Section: The Role Of Ethics Policy and Shared Values In The Perceived Image Of The Universitymentioning
confidence: 99%
“…The expert team consisted of a leading academic expert in international marketing and a practitioner working in the market research sector. Confectionary was selected because it is a category for which there are multiple, well-known local and foreign brands (Brečić et al, 2013). Eight were shortlisted that fulfilled two criteria: (a) the brand had never sponsored an event, or team in Croatia before, and (b) Croatians should have some knowledge of the brand and its Serbian roots.…”
Section: Brand Selectionmentioning
confidence: 99%
“…Variations are linked to a cultural context of newly (re)emerging states with high ethnocentrism, animosity and uneasy political relationships. Transnational brands, however, appear immune to much consumer ethnocentrism (Bre ci c et al, 2013).…”
Section: Theoretical Frameworkmentioning
confidence: 99%